2021
DOI: 10.3389/fendo.2021.657488
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Cholecystectomy and the Risk for Fracture: A Nationwide Population-Based Cohort Study in Korea

Abstract: ObjectivesTo evaluate the risk of fracture in individuals with a history of cholecystectomy in Korean population.MethodsIndividuals (n = 143,667) aged ≥ 40 y who underwent cholecystectomy between 2010 and 2015 and the controls (n = 255,522), matched by age and sex, were identified from the database of the Korean National Health Insurance Services. The adjusted hazard ratio (aHR) and 95% confidence interval (CI) of fracture were estimated following cholecystectomy, and a Cox regression analysis was performed.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Other non-MR studies have also reported varied conclusions [21][22][23][24][25] . Interpreting the above studies alongside our study results, which showed that only HMGCR inhibition, not NPC1L inhibition and PCSK9 inhibition, was correlated with a reduced risk of PD.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other non-MR studies have also reported varied conclusions [21][22][23][24][25] . Interpreting the above studies alongside our study results, which showed that only HMGCR inhibition, not NPC1L inhibition and PCSK9 inhibition, was correlated with a reduced risk of PD.…”
Section: Discussionmentioning
confidence: 97%
“…A handful of literature has explored the association between lipid-lowering drugs or serum lipid levels and PD, yet the results have been inconsistent [19][20][21][22][23][24][25][26] . In a MR study using a Danish dataset, no association was detected between LDL and the risk of PD, whereas a separate MR study conducted by a Swedish team suggested a causal inverse association of LDL with PD risk 19,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DM may lead to more severe liver inflammation and fibrosis progression [ 40 ]. DM might be mediated by binding of insulin-like growth factor-1 (IGF-1) to the IGF-1 receptor and activate mitogen-activated protein kinase (MAPK) and phosphoinositide 3-kinase/protein kinase B (PI3K/AKT) signaling pathways leading to increased cell proliferation and decreased apoptosis [ 41 ]. Insulin resistance (IR), which has a negative impact on antiviral therapy responses [ 42 ] and liver-related outcomes [ 43 ], plays a crucial role in fibrosis progression.…”
Section: Discussionmentioning
confidence: 99%
“…Cholecystectomy is a popular surgical operation, and patients who have had cholecystectomy are frequently encountered in clinical practice. Gallstones are the most common reason for cholecystectomy, followed by cholecystitis (Lee et al, 2021).…”
Section: Introductionmentioning
confidence: 99%